2013
DOI: 10.1159/000345359
|View full text |Cite
|
Sign up to set email alerts
|

The German Translation and Validation of the Scale for the Assessment of Thought, Language and Communication: A Factor Analytic Study

Abstract: The Scale for the Assessment of Thought, Language and Communication (TLC) represents an instrument for the assessment of formal thought disorder (FTD). The factorial dimensionality of the TLC has yielded ambiguous results for a distinction between positive (e.g. circumstantiality) and negative (e.g. poverty of speech) FTD. The purpose of the current study was to first translate and validate the TLC scale in German. Second, the internal structure was explored in order to identify different FTD dimensions. Two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Previous factor solutions of the TLC were somewhat variable, and three or more factor solutions have been extracted from several language versions of the TLC scale for schizophrenia patients [17,18,20]. Our findings are consistent with those of Nagel et al [42] who extracted a three factor solution reflecting disorganization, emptiness, and linguistic control factors for the German version of the TLC scale using 146 patients with diagnoses of schizophrenia, mania, and depression. The previously yielded factor structures for the various language versions of the TLC scale were as follows: for the English version, a five-factor structure reflecting disorganization, negative, stilted speech/word approximations, neologisms/clanging, and distractibility/blocking [20]; for the French version, a five-factor structure reflecting thinking disorganization, verbal production, verbal structure, stilted speech, and distractible speech/blocking factors [18]; for the Greek version, a three-factor structure reflecting disorganization of speech, peculiarities of speech, and verbosity factors [17].…”
Section: Discussionsupporting
confidence: 87%
“…Previous factor solutions of the TLC were somewhat variable, and three or more factor solutions have been extracted from several language versions of the TLC scale for schizophrenia patients [17,18,20]. Our findings are consistent with those of Nagel et al [42] who extracted a three factor solution reflecting disorganization, emptiness, and linguistic control factors for the German version of the TLC scale using 146 patients with diagnoses of schizophrenia, mania, and depression. The previously yielded factor structures for the various language versions of the TLC scale were as follows: for the English version, a five-factor structure reflecting disorganization, negative, stilted speech/word approximations, neologisms/clanging, and distractibility/blocking [20]; for the French version, a five-factor structure reflecting thinking disorganization, verbal production, verbal structure, stilted speech, and distractible speech/blocking factors [18]; for the Greek version, a three-factor structure reflecting disorganization of speech, peculiarities of speech, and verbosity factors [17].…”
Section: Discussionsupporting
confidence: 87%
“…FTD phenomena such as poverty of thought, tangentiality, and derailment are diagnostically unspecific; however, the severity and patterns of symptom formations have been found to diverge among diagnostic groups [1,2,3]. FTD can also be observed in healthy people, though its symptoms are less severe [3,4]; they can, however, be exacerbated, e.g. under mental stress, sleep deprivation, or the influence of psychotropic substances [5].…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation for the differences in items and factor structure could be due to translation bias and/or cross-cultural differences. Validation studies of translated health constructs repeatedly showed differences in factor structure and number of items (Hwang, Kim, Kim, Kim, & Ahn, 2013;Kim, DeCoster, Huang, & Bryant, 2013;Nagels et al, 2013). Cross-cultural differences were especially noticed between different ethnic populations, e.g., Korean and Greek (Hwang et al, 2013) or Hispanics and non-Hispanics (Sanchez & Vargas, 2016).…”
Section: Discussionmentioning
confidence: 99%